PREPARASI DAN KARAKTERISASI BAHAN KOMPOSIT POLIPROPILENA DENGAN PENGISI SERAT LIMBAH PADAT (FIBRE RECOVERY) DARI PABRIK PULP DAN KERTAS - bakar, abu (IAIN PADANGSIDIMPUAN, 2013)
AbstractThe research of preparing biodegradable composite materials from polypropylene (PP) filled by fibre recovery (FR) from solid waste pulp and paper mill with meleic anhydride (MAH) as coupling agent and benzoil peroxide (BPO) as initiator has been examined. In this study, fillers composition were variaed (PP:FR)%. Composites were obtained by reflux at 170Â°C for 3 hour and formed to film. The charaterization were done by tensile test, DTA, FT-IR, SEM, and biodegradable test. The result showed that the optimum ratio of composite PP-FR was (90:10)% with tensile strength 17.7 MPa. The tensile strength increased by adding 3% MAH, obtained optimum tensile strength 20.9 MPa at ratio (60:40)% and by adding BPO, the tensile strength more increased to 24.0 MPa at optimum ratio (70:30)%. The reason for this improvement was detected by FT-IR studies of esterification reactions between PP-MAH with filler FR. SEM studies of the surface showed better dispersion of fibres in the matrix, a more effective wetting of fibres by the matrix, and a better adhesion between the two phases. DTA result showed decreasing of decomposition temperature of composite materials.Key words : Polypropylene, fibre recovery, meleic anhydride